2011
DOI: 10.1177/0042098011427188
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Meaning of Neighbourhood Attachment in Chinese Commodity Housing Estates: Evidence from Guangzhou

Abstract: The housing reform in urban China since the 1990s and the ensuing spatial and social dynamics gave rise to new kinds of neighbourhoods with new logics of neighbouring and neighbourhood attachment. Meanwhile, neighbourhoods are actively promoted as platforms for policy implementation. Both are reasons to revisit the meaning of neighbourhood attachment in the Chinese context. This article focuses on the roles of neighbourly interaction and physical environment, juxtaposing postreform commodity housing estates ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 42 publications
(59 reference statements)
11
110
0
3
Order By: Relevance
“…In contrast, neighbourhoods with a more organised governance system and a stronger shared social identity such as commodity estates and work-unit neighbourhoods tend to have higher levels of social solidarity. These findings would also confirm earlier studies that private commodity estates do not lack social cohesion amongst its residents Pow, 2007;Yip, 2012;Zhu et al, 2012;Wang et al, 2015Wang et al, , 2016b.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, neighbourhoods with a more organised governance system and a stronger shared social identity such as commodity estates and work-unit neighbourhoods tend to have higher levels of social solidarity. These findings would also confirm earlier studies that private commodity estates do not lack social cohesion amongst its residents Pow, 2007;Yip, 2012;Zhu et al, 2012;Wang et al, 2015Wang et al, , 2016b.…”
Section: Resultssupporting
confidence: 90%
“…The purpose of such communities is often to defend against larger market actors such as private developers and property management agencies. Findings further show that commodity neighbourhoods have higher level of residential satisfaction and attachment (Breitung, 2012;Zhu et al, 2012). This is usually fostered by a shared social identity as middle-class homeowners belonging to a 'civilised' neighbourhood (Pow, 2007).…”
Section: Migrant Influx and Social Cohesion In Chinese Citiesmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast Li et al (2012) found that local networks are generally weaker in these commodity housing enclaves, although these have higher community attachment and neighbourhood satisfaction. Zhu et al (2012) have similar findings, and they attribute the higher neighbourhood satisfaction to the solidarity arising from homeownership.…”
Section: Models Of Neighbourhood Interactionmentioning
confidence: 59%
“…The editors of a recent special issue of this journal have diagnosed the ongoing practices as Enclave Urbanism, sparking a lively academic discourse around Chinese urban form (Breitung, 2012;Douglass, Wissink, & van Kempen, 2012;He, 2013;Hogan, Bunnell, Pow, Permanasari, & Morshidi, 2012;Jie Shen & Wu, 2012;Z. Li & Wu, 2013; *Email: deljana.iossifova@manchester.ac.uk Wang, Li, & Chai, 2012;Wissink et al, 2012;Wu, Zhang, & Webster, 2013a;Zhu, Breitung, & Li, 2012). But is this an accurate understanding of the emerging urban condition in China, or are alternative readings possible?…”
Section: Introductionmentioning
confidence: 99%